GDNF is an Endogenous Negative Regulator of Ethanol-Mediated Reward and of Ethanol Consumption After a Period of Abstinence - Carnicella, Sebastien (2009)
BACKGROUND: We previously found that activation of the glial cell line-derived neurotrophic factor (GDNF) pathway in the ventral tegmental area (VTA) reduces ethanol-drinking behaviors. In this study, we set out to assess the contribution of endogenous GDNF or its receptor GFRα1 to the regulation of ethanol-related behaviors. METHODS: GDNF and GFRα1 heterozygote mice (HET) and their wild-type littermate controls (WT) were used for the studies. Ethanol-induced hyperlocomotion, sensitization, and conditioned place preference (CPP), as well as ethanol consumption before and after a period of abstinence were evaluated. Blood ethanol concentration (BEC) was also measured. RESULTS: We observed no differences between the GDNF HET and WT mice in the level of locomotor activity or in sensitization to ethanol-induced hyperlocomotion after systemic injection of a nonhypnotic dose of ethanol and in BEC. However, GDNF and GFRα1 mice exhibited increased place preference to ethanol as compared with their WT littermates. The levels of voluntary ethanol or quinine consumption were similar in the GDNF HET and WT mice, however, a small but significant increase in saccharin intake was observed in the GDNF HET mice. No changes were detected in voluntary ethanol, saccharin or quinine consumption of GFRα1 HET mice as compared with their WT littermates. Interestingly, however, both the GDNF and GFRα1 HET mice consumed much larger quantities of ethanol after a period of abstinence from ethanol as compared with their WT littermates. Furthermore, the increase in ethanol consumption after abstinence was found to be specific for ethanol as similar levels of saccharin intake were measured in the GDNF and GFRα1 HET and WT mice after abstinence. CONCLUSIONS: Our results suggest that endogenous GDNF negatively regulates the rewarding effect of ethanol and ethanol-drinking behaviors after a period of abstinence.